Modeling the Process by Which People Try to Explain Complex Things to Others. (December 2021) - Klein, Gary; Hoffman, Robert; Mueller, Shane; Newsome, Emily
The process of explaining something to another person is more than offering a statement. Explaining means taking the perspective and knowledge of the Learner into account and determining whether the Learner is satisfied. While the nature of explanation—conceived of as a set of statements—has been explored philosophically and empirically, the process of explaining, as an activity, has received less attention. We conducted an archival study, looking at 73 cases of explaining. We were particularly interested in cases in which the explanations focused on the workings of complex systems or technologies. The results generated two models: local explaining to address why a device (such an intelligent system) acted in a surprising way, and global explaining about how a device works. The examination of the processes of explaining as it occurs in natural settings revealed a number of mistaken beliefs about how explaining happens, and what constitutes an explanation that encourages learning.